Final reporting of the feasibility study on a Caribbean shipping service (Caribbean Line Limited Port of SpainTT)
Reviews the outlook for the regional economies and the role that the shipping industry is likely to play. Proposes a maritime development strategy and recommends that three companies - Caricom Cargo Distribution Services Company; Maritime Holding Company and International Services Company be formed. Also recommends that provision be made within the Caricom Cargo Distribution Company for a reefer passenger service. Deals with topics such as projects discription; markets and marketing; organisation and management; investments, and start up activities. Records conclusions and recommendations.
DC